Necrosis Is the Dominant Cell Death Pathway in Uropathogenic Escherichia coli Elicited Epididymo-Orchitis and Is Responsible for Damage of Rat Testis - Lu, Yongning (Public Library of Science, 2013)
Male infertility is a frequent medical condition, compromising approximately one in twenty men, with infections of the reproductive tract constituting a major etiological factor. Bacterial epididymo-orchitis results in acute inflammation most often caused by ascending canalicular infections from the urethra via the continuous male excurrent ductal system. Uropathogenic Escherichia coli (UPEC) represent a relevant pathogen in urogenital tract infections. To explore how bacteria can cause damage and cell loss and thus impair fertility, an in vivo epididymo-orchitis model was employed in rats by injecting UPEC strain CFT073 into the vas deference in close proximity to the epididymis. Seven days post infection bacteria were found predominantly in the testicular interstitial space. UPEC infection resulted in severe impairment of spermatogenesis by germ cell loss, damage of testicular somatic cells, a decrease in sperm numbers and a significant increase in TUNEL (+) cells. Activation of caspase-8 (extrinsic apoptotic pathway), caspase-3/−6 (intrinsic apoptotic pathway), caspase-1 (pyroptosis pathway) and the presence of 180 bp DNA fragments, all of which serve as indicators of the classical apoptotic pathway, were not observed in infected testis. Notably, electron microscopical examination revealed degenerative features of Sertoli cells (SC) in UPEC infected testis. Furthermore, the passive release of high mobility group protein B1 (HMGB1), as an indication of necrosis, was observed in vivo in infected testis. Thus, necrosis appears to be the dominant cell death pathway in UPEC infected testis. Substantial necrotic changes seen in Sertoli cells will contribute to impaired spermatogenesis by loss of function in supporting the dependent germ cells.